1983
DOI: 10.1109/temc.1983.304166
|View full text |Cite
|
Sign up to set email alerts
|

Corrective Measures for Minimizing the Interaction of Power Lines with MF Broadcast Antennas

Abstract: New high-voltage power lines are often built in close proximity to MF/AM broadcast antennas. The "skywire" which joins the tops of the power-line towers creates closed loops for RF current on the power line and its image in ground, and these loops can be resonant in the MF band. If the broadcast antenna operates on such a resonant frequency, it induces large currents on the skywires and power-line towers, and "reradiation" from these induced currents can considerably alter the broadcast antenna's radiation pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 5 publications
1
18
0
Order By: Relevance
“…Considering that the smallest unit that constitutes a PTL is two adjacent power towers within a span and the ground wire connecting the power towers. Terefore, the study in [6] only calculated the induced current on the PTL within the representative span and found that the calculated result of the induced current was in good agreement with the measured result. For this reason, this paper also simplifes the simulation model in Figure 4 and only considers the PTL within a representative span in the subsequent calculation of the induced current.…”
Section: Induced Currents and Its Mode Decomposition Of Ptl In The Me...mentioning
confidence: 86%
See 1 more Smart Citation
“…Considering that the smallest unit that constitutes a PTL is two adjacent power towers within a span and the ground wire connecting the power towers. Terefore, the study in [6] only calculated the induced current on the PTL within the representative span and found that the calculated result of the induced current was in good agreement with the measured result. For this reason, this paper also simplifes the simulation model in Figure 4 and only considers the PTL within a representative span in the subsequent calculation of the induced current.…”
Section: Induced Currents and Its Mode Decomposition Of Ptl In The Me...mentioning
confidence: 86%
“…In this method, the power towers and the ground wires are equivalent to wire antenna models with diferent radii in diferent frequency bands, and the conductors could be ignored in the modeling because it is perpendicular to the direction of the excitation electric feld. Although these methods of simulation calculation can obtain the numerical value of the induced current on PTL, they cannot reasonably explain the variation of the induced current [6].…”
Section: Introductionmentioning
confidence: 99%
“…Based on loop antenna theory and the results reported in [15][16][17][18][19][20], Trueman C.W. et al explained the mechanism of RRI resonance in AM radio frequency band (535 kHz~1705 kHz) when towers are connected to grounding wires.…”
Section: Mechanism Of Rri Resonance and Estimation Of Resonant Frequementioning
confidence: 99%
“…According to [15][16][17][18][19][20], conventionally in 535~1,705 kHz, a tower is equivalent to a line antenna of 2.13~4.88 m. Trueman et al established the numerical model of a 500 kV double-circuit transmission line with V1S towers [20], as shown in Fig. 2.…”
Section: Towers Linked By Grounding Wiresmentioning
confidence: 99%
See 1 more Smart Citation